Faktor Yang Berhubungan Dengan Niat Santri Menjadi Kader POSKESTREN di Pondok Pesantren Darus Sunnah, Tangerang Selatan - Fitriah, Mita; Abassuni, Febrianti (Journal of Religion and Public Health, 2024)
The intention of students to become poskestren cadres is important to be knownespecially in recruiting cadres stage. It is related to attitude, subjective norms, andperceived behavioral control. This study aimed to determine the factors associated withthe intention of students to become poskestren cadres at Darus Sunnah Islamic Boarding School in South Tangerang City. It was a quantitative research with across-sectional analytic study design. Using proportional stratified random samplingtechnique, 86 respondents from the first grade of secondary level students to the second grade of senior high school were selected and interviewed. From the research, it was known that 57% of students intended to become poskestren cadres, 62.8% of students had positive attitudes, 58.1% of students had positive subjective norms, and 66.3% had positive perception of behavioral control. The results of the chi-square test showed that there was no relationship between attitude and intention of students to become poskestren cadres (Pvalue 0.145). Meanwhile, subjective norms (Pvalue 0.000) and perceived behavioral control (Pvalue 0.000) were associated with intention of students to become poskestren cadres. Based on the study result, it is recommended to the poskestren administrators to disseminate more information to students and their parents about poskestren cadres, especially about the benefits of becoming a poskestren cadre. From that, family and peers can share positive perception and can convince students to become cadres.Keywords: Poskestren, Human Resource Management, Theory of Planned Behavior